Ages of stellar populations in the low-metallicity star-forming dwarf galaxies - Guseva, N.G. (Кинематика и физика небесных тел, 2005)
We perform a comprehensive study of ten star-forming (SF) galaxies with the oxygen abundance Z<Z/20 [5] and blue extended low-surface-brightness components (LSB). Long-slit spectroscopy and V , I CCD photometry were obtained with the Kitt Peak 2.1-m and 4-m telescopes, the 4.5-m MMT, the 2.4-m HST and the 10-m Keck II telescopes. We use two extinction-insensitive methods based on the equivalent widths of (1) emission and (2) absorption Balmer lines to put constraints on the age of the stellar populations (SP). In addition, we use two extinction-dependent methods based on (3) the spectral energy distribution and (4) the (V – I) colour. Several scenarios of star formation were explored using all four methods. We compare the photometric and spectroscopic properties of the ten low-metallicity SF galaxies with those of a sample of 16 wellknown dwarf irregular and blue compact dwarf (BCD) galaxies. We show that there is a clear trend for the stellar LSB component of lower-metallicity galaxies to be bluer. However, the observed trend is too steep to be explained only by metallicity effects. Therefore, the lower-metallicity galaxies have also younger populations. In particular, the luminosity-weighted ages of galaxies with LSB colours of (V – I)<0.6 are not greater than 1–2 Gyr. Our finding is confirmed by analysing of high-redshift galaxies and the fossil record of the SPs of nearby galaxies: the stellar birthrate for most massive galaxies peaked at z > 1 (or ~10 Gyr) just as for low-mass galaxies efficient star formation have been triggered at z ~ 0.2 (or ~2 Gyr).